Peran Situs Sejarah melalui Pendekatan Project Based Learning dalam Meningkatkan Pemahaman Pembelajaran Sejarah Peserta Didik MAS Nurussa’adah Jakarta Selatan - Manda Azzahra; Rudy Gunawan (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
The role of historical sites in history learning has great potential to improve students' understanding through contextual direct learning experiences. However, in reality, history learning in schools is still dominated by conventional methods that are centered on teachers and textbooks, so that students' understanding of historical materials tends to be rote and less meaningful. This study aims to determine the role of historical sites through the Project-Based Learning (PjBL) approach in improving students' understanding of history learning at MAS (Swasta Madrasah Aliyah) Nurussa'adah, South Jakarta. This study uses a qualitative approach with a case study method. Data collection techniques are carried out through observation, interviews, and documentation. The learning project focused on visits to the National Museum and the Fatahillah Museum in Jakarta, which were adjusted to the history material for grade X. The results showed that students became more enthusiastic and active in the learning process, were able to understand the relationship between historical events and their legacies, and showed an increase in critical and collaborative thinking skills. In addition, the PjBL method based on historical sites strengthens students' understanding of national values ​​and the importance of preserving cultural heritage. These findings indicate that the integration of historical sites into learning through PjBL has a positive impact on students' understanding of history. Therefore, this approach can be used as an innovative alternative in improving the quality of history learning at the madrasah level.